GAMBARAN KEMAMPUAN MOTORIK HALUS ANAK USIA 4-5 TAHUN DALAM KEGIATAN MENGGUNTING DI TK KRISTEN CITRA BANGSA - Akoit, Florida Maria; Yuniati , Yohana; Kale , Sartika; Seran , Theodorina Novyani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Fine motor skills are an important aspect in the development of children aged 4–5 years related to the coordination of small muscles, especially fingers, in responding to visual stimuli. This study aims to analyze the role of scissoring activities in stimulating the development of fine motor skills in early childhood through five aspects, namely eye-hand coordination, finger strength and flexibility, precision of movement and neatness of results, independence, and concentration. The method used is a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. Then data collection is carried out through the stages of data reduction, information presentation, and conclusion drawing. The results of the study indicate that scissoring activities contribute positively to improving eye-hand coordination such as children being able to direct scissors along a line, finger strength and flexibility such as children being able to open and close scissors repeatedly, precision of movement and neatness of results such as cutting results following a line, concentration such as children focusing on one activity until it is finished, and independence namely children being able to cut independently without assistance. Therefore, scissoring activities are recommended as one of the effective stimulations in supporting the improvement of fine motor skills in early childhood.